Enhancing Elementary School Management: An Evaluation of Facilities and Infrastructure Management with CIPP Model - Rifan Budiyanto; Sri Marmoah; Karsono Karsono (STAI Hubbulwathan Duri, 2025)
Effective management of school facilities and infrastructure is essential for supporting quality education. This study evaluates how facilities and infrastructure are managed in elementary schools using the CIPP (Context, Input, Process, Product) evaluation model. A descriptive qualitative approach was used, with data collected through observations, interviews, and document analysis. The research was conducted at SD Negeri Tekaran 2, Wonogiri, Central Java, involving the principal and six teachers as participants. Data were analyzed using the Miles and Huberman model.Findings indicate that SD Negeri Tekaran 2 has adequate infrastructure, including well-equipped classrooms, a library, sports and arts facilities, sanitation, and technology resources. In the input phase, infrastructure management is supported by transparent budget planning, involving procurement, routine maintenance, and emergency allocations with expert involvement. The process involves periodic inspections, damage reporting, and asset inventory. In the product phase, well-maintained facilities have positively impacted learning outcomes, increased student motivation, and enhanced practical skills, fostering a supportive and effective learning environment.The study concludes that systematic and transparent management of school facilities significantly contributes to the quality of education in elementary schools. Well-maintained infrastructure not only supports teaching and learning but also enhances the overall educational experience and outcomes.